PS01.099: RETROSPECTIVE ANALYSIS OF CLINICAL FEATURES OF 202 CASES WITH ESOPHAGEAL FOREIGN BODIES. (14th September 2018) - Feng, Jinteng; Fan, Kun; Gao, Rui; Fu, Junke; Zhang, Guangjian
Abstract: Background: Esophageal foreign bodies refer to objects that are accidentally or intentionally swallowed, or that are naturally swallowed during medication or eating, temporarily staying in or resting in the esophagus. Esophageal foreign body is one of the common emergency of esophageal surgery, more common in the elderly and children. This paper study clinical features of esophageal foreign body in northwestern China in order to improve the abilities of diagnosis and treatment for the disease. Methods: Clinical data of 202 patients admitted in for esophageal foreign body was analyzed retrospectively. The general information of the patients were collected, and the types of foreign bodies, the location, diagnostic methods, methods of taking out and related complications, hospitalization days, et al were analyzed statistically. Results: The types of esophageal foreign body included jujube pit (61.8%), animal bones (12.9%) and non-food foreign bodies (24.3%). It mainly occurred in the upper orifice of the esophagus (65.8%). Diagnostic methods were mainly consisted of esophageal angiography (57.9%), chest X-ray (19.8%) and endoscopy (16.4%). Most of the patients (189, 93.6%) were treated with esophagoscopy. Altogether 26 cases presented with complications, and 18 of them were admitted in for jujube pit. Conclusion: The main cause of esophageal foreign body is jujube pit. Early diagnose and timely management is essential for the disease. How to guide the population as far as possible to avoid ingesting jujube pit wrongly and reduce the incidence of esophageal foreign body is of practical significance. Disclosure: All authors have declared no conflicts of interest.